Generation Z, Disruption and Algorithms: Doom Spending as a Social Practice Disposition of Youth : (A Phenomenological Study in Surabaya) - Margaretha Diah Ayu Trismindarti; Prilianti Tiurida Marbun; Rangga Prashagi; Nurlaela To Syifa Malika Rahma; Edy Purwanto (P3M POLITEKNIK NEGERI AMBON, 2025)
Generation Z is a community group that grows through digital interaction. This has caused a very rapid element of change, one of which is through consumption patterns that come from social media preferences. This dynamic provides a new space that is formed through doom spending, which is a culture of excessive shopping to overcome social anxiety and emotional distress that is considered prevalent. Based on this reality, this study aims to analyze and understand how doom spending works as an element of shifting consumption pattern disposition, contributing together with social media which is the lifestyle of Generation Z in the city of Surabaya. This study uses a qualitative method with Alfred Shcutz's phenomenological approach to obtain the meaning experienced by informants in the reality they face. Data was collected through a process of observation, interviews, and documentation with 7 Generation Z informants in the city of Surabaya who came from various statuses. The results of the interviews were processed using the N Vivo application to categorize the findings and integrate theoretical concepts with the reality in the field. Thus, this study provides findings that doom spending is a structured social practice and reflects the dynamics of habitus in the digital disposition of today's generation Z. Keywords: habitus, generation Z, social media, social practices, consumption